The Impact of Innovation Policy on the Sectoral Structure of the Estonian Economy - Ruud, Laura (Estonian Discussions on Economic Policy, 2009)
The current global economic crisis has increased the awareness of the role of knowledge-based economy in raising international competitiveness. For contributing to faster economic restructuring, knowing the quantitative effects of innovation policy decisions is relevant. Using an exports structure as an indicator of a production structure, a pooled data approach allows estimating the elasticity of the exports structure on innovation indicators. Admitting estimation limitations of the short time series available, the estimation results confirm a statistically significant effect of enterprises’ expenditures on research and development, and labour productivity on exports structure. The elasticity of the specialisation on higher technology intensity industries is generally higher than the elasticity of lower technology intensity industries. Knowing quantitatively confirmed effects in the past contributes to more effective competitiveness supporting policy decisions ahead.